Policy Gaps in the Development of Islamic Religious Education Teacher Professionalism in Aceh’s Special Autonomy Context - Salman Salman; Warul Walidin; T. Zulfikar; Syamsul Bahri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to analyze the development of PAI teacher professionalism in Aceh Government policies, the forms and implementation of these policies, and the challenges and solutions in strengthening PAI teacher professionalism in Aceh. This study employed a qualitative approach with a naturalistic inquiry design. Data were collected through observation, in-depth interviews, and documentation studies involving policy actors and field implementers, including academics, the Aceh Education Office (Dinas Pendidikan Aceh), the Aceh Education Council (Majelis Pendidikan Aceh), the Aceh House of Representatives (DPRA), the Legal Bureau of the Aceh Government, BPSDM Aceh, PAI teacher certification institutions, PAI supervisors, teacher associations, and senior high school PAI teachers. Data were analyzed inductively and conceptually through a critical dialogue between empirical findings and public policy theories, while regulatory texts were examined using a normative-hermeneutic approach. The findings show that Aceh has a strong legal foundation through the Law on the Government of Aceh and Aceh Qanun; however, no explicit professionalism model for PAI teachers has been formulated based on Aceh’s special autonomy. Policy implementation remains administrative and nationally oriented, while religious, cultural, and Islamic law dimensions are not yet systematically integrated. The study concludes that strengthening PAI teacher professionalism requires policy coordination, regulatory reform, and a substantive-religious professionalism model grounded in Aceh’s special autonomy.